Peningkatan Kualitas Pendidikan dan Pelestarian Lingkungan di Kampung Njawani - Adiyatama, Bima Prayoga; Gunawan, Christian Tedric; Saputra, Dandra Wahyu; Kristiawan, Davar Abednego; Romanzah, Dede; Hazim, Dhimas Aziz Ahmad; Pardomuan, Dimas Marchelino; Safitri, Elsa; Widiasari, Meirliana; Hartono, Otniel Oktavianus; Sulistyaningrum I, Cicilia Dyah (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Njawani Village, located in Banjarsari District, Surakarta Regency, is one of the villages that has a wealth of culture and traditions that are highly valued by its people. This village is known for its various traditional art performances such as dances, gamelan, and wayang kulit performances. The main theme of this KKN program is "Improving Access and Quality of Education in the Community." In order to carry out this theme, KKN students collaborate with the local community to raise awareness of the importance of education and the role of a clean and well-maintained environment. The community service program carried out by UNS KKN students group 251 in Njawani Village succeeded in achieving its main goal, namely improving the quality of education and environmental awareness of the community. Several programs implemented, such as the creation of a mural creation space, managing organic waste into compost, and making pots from waste, have a positive impact on the community.